HUBUNGAN ANTARA ACADEMIC SELF-EFFICACY DENGAN CAREER ADAPTABILITY PADA MAHASISWA TINGKAT AKHIR DI JAKARTA - Jessica, Joanna; Kembaren, Esther Muliana (MANASA, 2024)
One of the major problems in Indonesia is the high unemployment rate, including among undergraduates. In 2023, the undergraduate unemployment rate was approximately 958,000, or 12% of the total rate. Several factors affect an individual's ability to get a job. One of them is career adaptability, the process of achieving career goals that needs to be developed since undergoing education, especially in final-year students. However, little effort has been made to improve students' career adaptability, such as academic self-efficacy. The purpose of this study is to examine the relationship between academic self-efficacy and career adaptability in final-year students in Jakarta. A correlational quantitative method was applied to 121 final-year students in Jakarta obtained through convenience sampling techniques. The measuring tool used to measure academic self-efficacy is The Academic Self-Efficacy Scale (TASES) which has gone through a validity test with a corrected-item total correlation score in the range of .384-.602 and Cronbach's alpha reliability score of .885. Meanwhile, the measuring tool for career adaptability is the Career Adapt-Abilities Scale (CAAS) with validity test results in the range of .322-.652 and a reliability score of .905. Based on the results of the correlation test with Spearman's correlation, there was a significant positive relationship between academic self-efficacy and career adaptability in final-year students in Jakarta, with a Spearman's Rho score of .636, p-value < .01. It can be concluded that the higher the academic self-efficacy, the higher the career adaptability of final-year students. Self-confidence in academic ability helps individuals prepare for future careers.